Cocaine, amphetamine, or titin: Unraveling the genetic underpinnings of dilated cardiomyopathy - Binay Kumar Panjiyar; Nikita Changlani; Clarisa Medina; Lisa R. Trevino (Clinical Case Reports, 2024)
Key Clinical Message An interesting case that shows the importance of identifying a pathogenic TTN gene mutation through genetic assessment in unexplained cardiomyopathy, especially with family history. This case highlights the need for genetic counseling and testing for at‐risk relatives, and advocates for personalized management considering both genetic and lifestyle factors. Abstract This case report examines a 33‐year‐old Hispanic male with bipolar disorder, schizophrenia, and a history of substance use, presenting with acute respiratory failure and cardiac arrest. The patient's nonischemic dilated cardiomyopathy (DCM) highlights the critical role of genetic factors, particularly titin gene (TTN) mutations, in cardiomyopathy pathogenesis. Through genetic analysis, we explore the intersection of lifestyle factors and genetic predisposition in DCM, underscoring the importance of comprehensive genetic testing for accurate diagnosis and targeted therapy. This case contributes to the evolving understanding of DCM etiology, emphasizing the necessity of considering both environmental and genetic factors in clinical assessment and management.